Dataset of aquatic insects acquired using field-emission scanning electron microscopy and the NanoSuit method - Yasuharu Takaku; Chiaki Suzuki; Takahiko Hariyama (Scientific Data, 2024)
Abstract A simple surface modification, called NanoSuit, by electron beam or by plasma irradiation can form a nanoscale layer, allowing to keep small animals alive and hydrous under the high vacuum required for field-emission scanning electron microscopy (FE-SEM). We previously applied NanoSuit to aquatic insects, Dixa longistyla larvae (Diptera: Dixidae), which always lie on their ventral surface just under the water surface. We found that the crown-like structures on the ventral side of the hind segments enable the larvae to reside in such ecological niche. Moreover, fine structures in the crown protected with NanoSuit appeared intact, unlike those subjected to conventional sample fixation. However, a fundamental understanding of these structures (living and/or not treated with conventional fixation) interacting directly with water should be established using FE-SEM. This data descriptor introduces a rich dataset of images acquired using NanoSuit for various aquatic insects. The image data can be accessed and viewed through Figshare.